Finding the elusive and causative autoantibody: An atypical case of autoimmune hemolytic anemia. Issue 4 (2nd February 2015) - Fetzko, Stephanie; Ahmed, Asra; Cooling, Laura
Key Clinical Message An isolated IgA‐mediated autoimmune hemolytic anemia can present a diagnostic challenge. When a routine direct antiglobulin test (DAT) is negative but clinical suspicion remains high, further testing with monospecific antisera should be performed. As with IgG‐mediated WAIHA, steroids are first‐line treatment, though splenectomy is often required to achieve a durable treatment response.